2008
DOI: 10.1021/jp803078y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Destruction of Propane in a Low-Temperature Plasma by the Addition of Unsaturated Hydrocarbons: Experiment and Modeling

Abstract: The oxidative destruction of propane at low temperature ( approximately 150 degrees C) in a nonthermal, atmospheric pressure plasma can be significantly enhanced without the use of a catalyst by the simple addition of an unsaturated alkene. An enhancement in the destruction of propane of up to 45% can be achieved by the addition of propene. Propene acts as a supply of OH radicals, which accelerate the breakdown of the propane. Ethene also enhances the destruction of propane but to a more limited extent. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…1-Nitronaphthalene and 2-nitroethenylbenzene are trace products in an air discharge, which indicate that reactions between some intermediates and NO and NO 2 take place in the destruction process. Whitehead et al 11 and Kushner et al 53 investigated the reactions between NOx and low carbon hydrocarbons such as C 3 H 6 and C 3 H 8 in the discharge by analyzing the kinetic data of these reactions. They found that NOx generated in the plasma can react with some hydrocarbon radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Nitronaphthalene and 2-nitroethenylbenzene are trace products in an air discharge, which indicate that reactions between some intermediates and NO and NO 2 take place in the destruction process. Whitehead et al 11 and Kushner et al 53 investigated the reactions between NOx and low carbon hydrocarbons such as C 3 H 6 and C 3 H 8 in the discharge by analyzing the kinetic data of these reactions. They found that NOx generated in the plasma can react with some hydrocarbon radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Naphthalene in flue gas can be treated effectively by electron beam irradiation, but the electron beam generation system and irradiation flow system are complicated. As an alternative approach, nonthermal plasma technology has been utilized for volatile organic compounds (VOCs) remediation for many years. Because of the large number of high energy electrons and radicals and relative low gas temperature, nonthermal plasma is regarded as a promising technology for gas phase pollutants destruction. In this study, we study the naphthalene decomposition efficiency by gliding arc discharge, which has been utilized for abatement of some other gas pollutants and considered as an efficient kind of nonthermal plasma by many scientists.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing temperature, the energy barrier for reaction on the catalytic surface, can be overcome more easily increasing the oxidation rate of the propane or propene. This is in addition to the increased rates for the gas-phase destruction of propane and propene by O and OH that occur with increasing temperature [21]. In this regime, thermal activation of the catalyst becomes more important overtaking the contribution of the plasma-activated processes.…”
Section: Discussionmentioning
confidence: 99%